Determining the distribution of pharmaceutically active compounds (PhACs) in soils and sediments by pressurized hot water extraction (PHWE). (October 2017) - Biel-Maeso, Miriam; Corada-Fernández, Carmen; Lara-Martín, Pablo A.
Abstract: The occurrence of pharmaceutically active compounds (PhACs) in the environment may pose a potential risk for humans and ecosystems. Wastewater treatment plants (WWTPs) are recognized as one of the main sources of these chemicals into both aquatic and terrestrial environments. The objectives of the study were to determine the presence of a wide variety of PhACs (n = 45) in sewage-impacted sediments and soils from the Guadalete River basin (SW Spain) by developing and applying an environmentally friendly multi-residue method based on pressurized hot water extraction (PHWE). Different parameters were optimized, including extraction temperature, pH, solvents, and clean-up. Extraction recoveries were analyte dependent, varying between 50% and 140% for most of the analytes when using pure water as extraction solvent at 100 °C. Determination of PhACs was performed by ultra-high performance liquid chromatography – tandem mass spectrometry (UPLC-MS/MS), enabling method detection (mLODs) and quantification (mLOQs) limits between <0.01 and 0.83 ng g −1 and from 0.02 to 2.75 ng g −1, respectively. Regarding the sampling area, 14 out of 45 target compounds were detected in soils and sediments. Analgesic/anti-inflammatories was the therapeutic group most commonly detected, reaching concentrations up to 20 ng g −1 . Highlights: Hot water as extraction solvent can be used for analysis of PhACs in solid matrices. Baseline contamination data for pharmaceuticals in Guadalete River basin is provided. 14 out of 45 pharmaceuticals compounds were found in analyzed samples. Analgesics/anti-inflammatories were predominant over other PhAC classes. PhACs were detected not only in surface soils but also at 25 cm depth.